Study on Graph Entropy Associated with Multilevel Atomic Excitation - Abu Mohamed Alhasan (New Ideas Concerning Science and Technology Vol. 8, 2021)
A graph-model is presented to describe multilevel atomic structure. As an example, we take the double L configuration in alkali-metal atoms with hyperfine structure and nuclear spin , as a graph with four vertices. Links are treated as coherence. We introduce the transition matrix which describes the connectivity matrix in static graph-model. In general, the transition matrix describes spatiotemporal behavior of the dynamic graph-model. Furthermore, it describes multiple connections and self-looping of vertices. The atomic excitation is made by short pulses, in order that the hyperfine structure is well resolved. Entropy associated with the proposed dynamic graph-model is used to identify transitions as well as local stabilization in the system without invoking the energy concept of the propagated pulses.